Vinculin and the mechanical response of adherent fibroblasts to matrix deformation. Issue 1 (December 2018) - Rosowski, Kathryn; Boltyanskiy, Rostislav; Xiang, Yingjie; Dries, Koen; Schwartz, Martin; Dufresne, Eric
Abstract Cells respond to the mechanics of their environment. Mechanical cues include extracellular matrix (ECM) stiffness and deformation, which are primarily sensed through integrin-mediated adhesions. We investigated the impact of ECM deformation on cellular forces, measuring the time-evolution of traction forces of isolated mouse fibroblasts in response to stretch and release. Stretch triggered a marked increase of traction stresses and apparent stiffness. Expression of the focal adhesion protein vinculin not only increased baseline traction forces, but also increased dissipation of mechanical energy, which was correlated with the cells' failure to recover baseline traction forces after release of stretch.